Formation of A. S. Pushkin’s Creative Personality in the Mirror of Yu. N. Tynianov’s Novel “Pushkin” - Ye. Sun (Научный диалог, 2018)
The features of the image of the formation of Alexander Pushkin’s creative personality in Yu. Tynyanov’s novel “Pushkin” are investigated. The question of realization Yu. Tynyanov’s creative concept in this work is raised. Tynyanov sought to escape from the prevailing of the absolutization of the individual and the work of the poet in literary studies of the time and create his own interpretation based on comparative historical and formal approaches. The author of the article points out that the writer depicts the poet as an unusual child deprived of love and understanding of relatives and, as a consequence, lonely. Attention of Yu. Tynianov to the origins of the creative personality is emphasized. It is shown that the writer refers to the description of how the boy masters the art of watching and reflecting, how he awakens the love of literature and folk art, develops a tendency to poetry. It is noted that Yu. Tynyanov’s interpretation of Pushkin’s childhood is sometimes distressing, but in the description of the youth perspective of the narrative changes: in Lyceum, overcoming the drama of his awareness of the differences from others, the young poet begins to understand the value and purpose of creative personality. The conclusion about the links between the principles of image formation of the poet’s personality and Yu. Tynyanov’s concept of historicity is made.